2013
DOI: 10.5935/abc.20130188
|View full text |Cite
|
Sign up to set email alerts
|

Does the Aging Process Significantly Modify the Mean Heart Rate?

Abstract: BackgroundThe Mean Heart Rate (MHR) tends to decrease with age. When adjusted for gender and diseases, the magnitude of this effect is unclear. ObjectiveTo analyze the MHR in a stratified sample of active and functionally independent individuals. MethodsA total of 1,172 patients aged ≥ 40 years underwent Holter monitoring and were stratified by age group: 1 = 40-49, 2 = 50-59, 3 = 60-69, 4 = 70-79, 5 = ≥ 80 years. The MHR was evaluated according to age and gender, adjusted for Hypertension (SAH), dyslipidemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Resting heart rate declined with age in the present study, as is consistent with cross-sectional [22,23] and longitudinal [24] data. The findings of these studies suggest that the decreased adrenergic response with aging is an important mechanism related to lower resting pulse rate and its protective effect [22][23][24].…”
Section: Time Trends In Ecg Findings Of Subjectssupporting
confidence: 92%
“…Resting heart rate declined with age in the present study, as is consistent with cross-sectional [22,23] and longitudinal [24] data. The findings of these studies suggest that the decreased adrenergic response with aging is an important mechanism related to lower resting pulse rate and its protective effect [22][23][24].…”
Section: Time Trends In Ecg Findings Of Subjectssupporting
confidence: 92%
“…Arrhythmia is a common occurrence of aging [ 20 , 21 ]. Bradycardia has been reported in younger patients and may not require immediate intervention if symptomatically mild [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In [ 49 ], for instance, it is reported how young adults and older adults present differences in emotional reactivity when positive or negative emotions are elicited by movies. The authors of [ 50 , 51 ] reported that the average heart rate of a subject as well as his/her heart rate variability tends to decrease with age. In [ 52 ], it is shown how the gait pattern of a subject during different cognitive load tasks tends to become less regular with the increase in the subject’s age.…”
Section: State Of the Artmentioning
confidence: 99%